Public Relations Campaign Strategy for The Covid 19 Vaccine by The Government of West Java - Khoiruddin Muchtar; Dudi Rustandi; Bahrudin Bahrudin; Ridwan Mubarok (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung Sunan Gunung Djati Bandung, 2022)
The government carries out a covid19 campaign by communicating continuously to the public. Communication is carried out within a certaiperiodme, so the community is motivated to participate in the program. This research aims to understand the West Java provincial government's public relations campaign strategy in the Covid-1919 Vaccination Campaign, which consists of planning, implementation, and evaluation. The research method uses a qualitative case study approach. Based on research results, the public relations campaign strategy carried out by the West Java government was carried out through several things, namely planning, implementation and evaluation. Planning consists of message planning, media planning, and time planning. The implementation consists of outreach, use of state media, and involvement of the Jabar Saber HoaxAt the same time, and the evaluation is done by looking at the campaign's success. Its significance lies in the use of public relations campaign strategies. Meanwhile, the limitations are that the Public Relations campaign strategy is relatively common, so it has little uniqueness. Combining conventional and digital approaches in public relations campaigns must be more comprehensive